FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT PEMBELIAN PRODUK PELAYANAN OPERATOR SELULER - Rahmanita, Rahmanita; Mustofa, Dedi Hendra (Journal of Accounting and Management Innovation, 2019)
The telecommunications services business has experienced rapid growth from year to year, this has encouraged cellular operators to launch various service package product programs. The number of service packages offered is sometimes quite confusing consumers, thus encouraging consumers to compare services offered for get the most profitable service. The phenomenon encourages this research which aims to analyze the factors that influence purchase intention cellular operator service products. Factors analyzed include product perceived quality, customer satisfaction, online advertising and e-wom. This study uses sample of 250 respondents who use cellular operator services. The statistical method used in analyzing data is a multiple regression model. The research data that has been collected is tested using the SPSS program. Hypothesis test results show product perceived quality, customer satisfaction, online advertising and e-wom simultaneously affect the purchase intention of cellular service products. Partially, only product perceived quality and customer satisfaction have significant positive effect on the intention to purchase cellular service products. In order for consumers' intention to buy service products to increase, telecommunication service providers need to improve the quality of products that consumers feel by providing a type of value-added services and increasing consumer satisfaction by expanding the type of service.Keywords:product perceived quality, customer satisfaction, online advertising, e-wom, purchase intention